Impacts of construction materials and site activities to the neighbourhood environment - Chan, Han Wang (2023)
Construction sites will unavoidably disrupt local residents' daily life and affect the surrounding environment. The purpose of this study is to provide an overview of the impact of construction materials and site activities on the neighbourhood environment and to assess the extent to which Malaysian construction industry are complying with the Malaysian Building By-Laws and Acts. A total of 16 construction material used and on-site activities performed, 9 major impacts and 6 different fields of requirement by Malaysian Building By-laws and various acts that need to be complying in order to mitigate the neighbourhood environmental impacts were identified through comprehensive literature review from published researchers. A detailed questionnaire was distributed to the construction industry practitioners within Klang Valley region and a total of 121 fully completed samples were collected from the survey, with an overall response rate of 60.5%. The data collected was analyzed statistically by SPSS. The overall ranking for the top 5 most influential construction materials and on-site activities are: (1) dust from exposed areas of cement and sand, (2) demolition and material handling, (3) transporting of fill on public roads, (4) excavation and placement of the fill in stock piles or to embankment and tied (5) driving piles and vehicle activity on dry unsealed roads. The overall ranking for top 5 impacts that affecting neighbourhood environment are: (1) noise generation; (2) dust generation; (3) damaged public road; (4) construction traffic and; and (5) mosquitoes from stagnant water. Moreover, factor analysis successfully identified 6 underlying factors (air pollution control; water pollution control, noise pollution control; construction traffic management; construction waste management; and mosquitoes control) from 22 practices of neighbourhood environment control. This paper aims to investigate in extent of compliance of the Malaysian construction industry with regard to neighbourhood environmental pollution to understand whether they are doing or following all the prevention strategies that determine by various acts. It provides insights and raises the awareness of the construction industry and society on the control practices of the Malaysian construction industry's impact on the neighbourhood environment.